Determinants of cigarette smoking and smoking frequency among women of reproductive age in Nigeria: evidence from a nationwide cross-sectional survey - Daniel Chukwuemeka Ogbuabor; Alphonsus Ogbonna Ogbuabor; Matthew Chibunna Igwe (BMC, 2023)
Abstract Background Smoking is a leading cause of avoidable deaths and attributable disability-adjusted life years globally. Yet, the determinants of smoking practices among women are understudied. This study assessed the determinants of smoking and smoking frequency among women of reproductive age in Nigeria. Methods and materials Data from the 2018 Nigeria Demographic and Health Survey (NDHS) were used in this study (n = 41,821). The data were adjusted for sampling weight, stratification, and cluster sampling design. The outcome variables were smoking status and smoking frequency (daily smoking and occasional smoking). The predictor variables included women's socio-demographic and household characteristics. Pearson's chi-squared test was used to evaluate the association between outcome and predictor variables. All variables significant in bivariate analyses were further analysed using complex sample logistics regression. Statistical significance was set at a p-value < 0.05. Results The prevalence of smoking among women of reproductive age is 0.3%. The prevalence of smoking frequency is 0.1% (daily) and 0.2% (occasionally). Overall, women aged 25-34 (AOR = 2.13, 95%CI: 1.06-4.29, ρ = 0.034), residing in the South-south region (AOR = 9.45, 95%CI: 2.04-43.72, ρ <0.001), being formerly married (AOR = 3.75, 95%CI: 1.52-9.21, ρ = 0.004), in female-headed households (AOR = 2.56, 95%CI: 1.29-5.08, ρ = 0.007) and owning mobile phones (AOR = 2.10, 95%CI: 1.13-3.90, ρ = 0.020) were more likely to smoke. Whereas female-headed households (AOR = 4.34, 95%CI: 1.37-13.77, ρ = 0.013) and being formerly married (AOR = 6.37, 95%CI: 1.67-24.24, ρ = 0.007) predisposed to daily smoking, age 15-24 (AOR = 0.11, 95%CI: 0.02-0.64, ρ = 0.014) was protective of daily smoking among women. Owning mobile phones (AOR = 2.43, 95%CI: 1.17-5.06, ρ = 0.018) increased the odds of occasional smoking among women. Conclusions The prevalence rates of smoking and smoking frequency are low among women of reproductive age in Nigeria. Women-centred approaches to tobacco prevention and cessation must become evidence-informed by incorporating these determinants into interventions targeting women of reproductive age in Nigeria.